Development strategy of pamelo orange processed agro-industry in Pangkep District with SWOT and AHP methods - Andi Ridwan Makkulawu; Soemarno Soemarno; Imam Santoso; Siti Asmaul Mustaniroh (Cita Konsultindo Research Center, 2023)
The aim of this research is to determine the development strategy for agro-industry of processed pomelo citrus products in Pangkep district. The method used is a combination of SWOT and AHP methods. SWOT is used to get the development strategy, while AHP is used to get product ranking. The results obtained from the swot analysis on the decision system to determine the strategy with coordinate points located at (-0.27; 0.11) (S-T) and while in the AHP method, the sub criteria are the results obtained in the decision system to determine product priorities feasible to be developed, namely Candy Oranges with a priority weight of 0.705. The conclusion of this study is that the combination of the SWOT and AHP methods can be used in determining the pomelo citrus agro-industry development policy in Pangkep district.